Coulson and Richardson's chemical engineering. Vol. 2, - Richardson, J. F. (Butterworth-Heinemann, 2002)
Chemical Engineering Volume 2 covers the properties of particulate systems, including the character of individual particles and their behaviour in fluids. Sedimentation of particles, both singly and at high concentrations, flow in packed and fluidised beads and filtration are then examined. The latter part of the book deals with separation processes, such as distillation and gas absorption, which illustrate applications of the fundamental principles of mass transfer introduced in Chemical Engineering Volume 1. In conclusion, several techniques of growing importance - adsorption, ion exchange, chromatographic and membrane separations, and process intensification - are described. * A logical progression of chemical engineering concepts, volume 2 builds on fundamental principles contained in Chemical Engineering volume 1 and these volumes are fully cross-referenced * Reflects the growth in complexity and stature of chemical engineering over the last few years * Supported with further reading at the end of each chapter and graded problems at the end of the book.
Previous ed. published as: Chemical engineering. Oxford : Pergamon, 1991.
Keywords: Particles.; Separation (Technology); Chemical engineering.; elektronické knihy; electronic books